Big Data Analytics for Cultural Heritage (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In this edition, we focused on big data analytics methods and tools that have been specifically developed for the domain of cultural heritage, as well as on experiences from the adaptation and/or application of general-purpose solutions in the domain of cultural heritage. The aim was to gather solutions, but also to summarise the lessons learnt, methodologies, and good practices that researchers and practitioners can use as a basis for their own work in the domain.